Pilih Sekolah atau Nikah? Self Awareness dan Edukasi Pencegahan Perkawinan Anak di Desa Cinangneng, Kabupaten Bogor - Titien Yusnita; Susri Adeni; Miftahul Anwar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
The child marriage rate is quite high above 40% during the 2019 period in Bogor Regency. This community service aims to educate school-age children to have an awareness that education is important for their future. Children should be given sufficient knowledge about the impact of child marriage which does not guarantee a better future for them. The impact of child marriage is the threat to reproductive health due to giving birth at a young age. The method of implementing the service is face-to-face, giving directions, counseling and simulations to school-age children who are vulnerable to child marriage and asking questions and exploring their opinions about child marriage and education so that it is expected that self-awareness will arise on the importance of education and delaying marriage at a young age. The results of this service activity show that school-age children are able to understand the material presented by the speaker and know that education is important for their future. This can be seen from the questions submitted by the participants and the presence of community leaders who support the importance of education. Keywords: Child, School-age Children, Child Marriage, Self Awareness